Challenges and opportunities for wheat alternative grains in breadmaking: Ex-situ- versus in-situ-produced dextran. (July 2021) - Wang, Yaqin; Maina, Ndegwa Henry; Coda, Rossana; Katina, Kati
Abstract: Background: The use of grains as an alternative to wheat in breadmaking has rapidly grown in the last few years, driven by the Sustainable Development Goals toward improving food security and promoting sustainable agriculture. Flours from legumes, pseudo-cereals, minor cereals and milling by-products, such as bran, are of particular interest. The production of partially substituted or wheat-free bread is, however, a challenging task in terms of texture and flavour attributes. Scope and approach: The present review covers recent advances in the application of dextrans in improving dough rheology, baking performance and bread flavour characteristics. Emphasis has been given to in situ application of dextran via sourdough technology as a 'clean label' alternative to commercial hydrocolloid additives. Key findings and conclusions: In-situ dextran production leads to bread with higher specific volume, softer crumbs and increased moisture content. Dextran also provides an anti-staling effect attributable to its ability to reduce water mobility and retard starch retrogradation. A structure–function relationship has suggested that dextran with high molecular weight and less branching is superior in enhancing bread quality. Furthermore, mild acidification favours the functionality of dextran in dough and bread systems, while intensive acidification results in adverse effects. Lactic acid bacterial strains belonging to the genus Weissella exhibiting mild acidification are therefore appreciated in regard to the utilisation of in-situ produced dextran. This review highlights the novel application of dextran as a flavour masking agent to minimise off-flavours (e.g. beany flavour, bitter taste, and aftertaste) originating from non-wheat grains, consequently improving the acceptability of the final products. Highlights: Producing high quality breads from non-wheat flours is a technological challenge. In situ produced dextran is a clean label alternative to commercial hydrocolloids. Dextrans modify dough rheology and improves bread textural quality and shelf-life. Dextrans can mask the off-flavours originating from non-wheat flours. Dextran structure and dough acidity are critical factors for in situ application.